HUKUM MENJAMAK SHALAT SAAT TAMPIL PADA KARNAVAL (Ahkam: Jurnal Hukum Islam, 2022)
Plural prayer is one of the reliefs for Muslims who find it difficult to carry out prayer times on time. In contrast to the time of the Prophet, in this era there are many increasingly complex conditions that make it difficult to perform prayers on time. Scholars differ on the category of difficulty or the reasons for the permissibility of plural prayers in the conditions of today. One of these conditions is performing at the carnival. It is very possible for carnival participants praying not on time due to several reasons, example thick makeup that does not allow ablution, complicated traditional clothing so that they cannot wear the mukena, and so on. This study aims to explain the meaning of plural prayer, the meaning of carnival, the law of carnival in the view of Islam, and the law of plural prayer when performing a carnival. The research method used is qualitative with a literature approach especially according to classical scholars. Using data analysis techniques and then described descriptively with relevant data sources. The results of the study explain that carnival cannot be a reason for someone to pray multiple prayers because carnival is only an entertainment, not a necessity.